2006
DOI: 10.1007/s00005-006-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

ETS transcription factors and regulation of immunity

Abstract: The ETS family is a diverse group of transcription factors that control the expressions of genes that participate in an array of cellular activities, ranging from mitosis to apoptosis. As a consequence of regulating these processes, most ETS factors are oncogenic. However, there is growing evidence that ETS factors are also essential to regulation of the immune system. Of the 29 recognized ETS factors, nine are known to regulate genes involved in immunity, including Ets1, Ets2, GABP, Fli1, Elf1, MEF, ESE1, PU.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
122
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 195 publications
4
122
0
3
Order By: Relevance
“…These findings fit well with the current understanding of the role of the transcription factors of the ETS family in controlling the expression of a wide variety of genes in hemopoietic and other cell types (13)(14)(15). Ets factors share a common DNA binding motif, the ets domain, which has been shown to be a variation of the winged helix-turn-helix motif (35).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings fit well with the current understanding of the role of the transcription factors of the ETS family in controlling the expression of a wide variety of genes in hemopoietic and other cell types (13)(14)(15). Ets factors share a common DNA binding motif, the ets domain, which has been shown to be a variation of the winged helix-turn-helix motif (35).…”
Section: Discussionsupporting
confidence: 85%
“…Ets-2 is a member of the ETS family of transcription factors that bind to purine-rich DNA sequences with GGA(A/T) as a central core consensus through a highly conserved DNA binding domain (13,14). Ets proteins function as activators or repressors of transcription in partnership with other DNA-binding proteins and coregulators and control the expression of genes involved in diverse biological functions, such as mitosis, growth, development, differentiation, apoptosis, and regulation of immunity (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Ets-2 plays an important role in the maturation, proliferation, and survival of mouse thymocytes, possibly by regulating the expression of c-Myc (23).…”
mentioning
confidence: 99%
“…The region contains 2 ETS transcription factors, ETS1 and FLI1. Known to be involved in the pathogenesis of multiple human cancers, 12,13 both ETS1 and FLI1 have an important role in the development of lymphoid tissues and immune system control, [14][15][16] regulating the activity of important players in B-cell growth and maturation such as the B-cell-specific activator protein PAX5 17,18 and the master regulator of plasma cell differentiation, PRDM1. 19 Notably, Ets1 and Fli1 are repressed during the late phases of B-cell differentiation in an in vitro murine system.…”
Section: Introductionmentioning
confidence: 99%
“…As knowledge of the immune defenses in PCa remains incomplete, we recently reported the identification of immunity-related genes in PCa, and suggested (based on bioinformatical analysis) that the genes are potentially regulated by members of the ETS family of transcription factors (7), which are known to be involved in translocations frequently found in PCa (8), and are reported to be essential for the regulation of immunity-related genes (9). More specifically, our analysis revealed that 31 out of the 37 immunity-related genes that we have identified have potential binding sites for the ETS family prototype, ETS-1 (7).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our analysis of the promoter regions of the identified immunity-related genes revealed that 31 out of the 37 genes have potential binding sites for the ETS family prototype, ETS-1 (7). In the majority of PCa cases, recurrent gene fusions involving members of the ETS family have frequently been reported (8), along with reports suggesting that members of the family are essential for the regulation of the immune system and immunity-related genes (9).…”
Section: Introductionmentioning
confidence: 99%